2022
DOI: 10.3390/ani12162100
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Effects of Edible Microalgae in a Canine Gut Model

Abstract: Microalgae are a source of bioactive compounds having recently been studied for their possible application as health-promoting ingredients. The aim of the study was to evaluate in an in vitro canine gut model the effects of four microalgae, Arthrospira platensis (AP), Haematococcus pluvialis (HP), Phaeodactylum tricornutum (PT) and Chlorella vulgaris (CV), on some fecal microbial populations and metabolites. The four microalgae were subjected to an in vitro digestion procedure, and subsequently, the digested b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 70 publications
0
6
0
Order By: Relevance
“…Microalgae samples were digested in triplicates. These supernatants and pellets were obtained from our previous study [ 15 ].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Microalgae samples were digested in triplicates. These supernatants and pellets were obtained from our previous study [ 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…In this research, the term bioaccessibility is used to define the fraction of iron released from the algal biomass during the in vitro digestibility analysis performed by Delsante et al (2022) [ 15 ]. To determine the bioaccessible iron fraction, the following equation was used: ([Fe] supernatant/[Fe] algal biomass) × 100 …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To the authors’ knowledge, an in vitro study conducted on macrophages isolated with bronchoalveolar lavage in cats demonstrated increased macrophage phagocytic activity when incubated with Escherichia Coli and exposed to a water-soluble extract of A. platensis [ 26 ], whereas a recent study performed in dogs showed an immune-stimulating activity of A. platensis when they were fed an extruded diet supplemented with 0.2% DM spray-dried Spirulina compared to the control group: dogs fed diets supplemented with Spirulina showed significantly higher vaccine response and higher levels of fecal IgA than the control group [ 27 ]. Another recent publication [ 28 ] assessed the effect of four edible microalgae, including A. platensis , in a canine gut in vitro mode; the authors concluded that the microbial saccharolytic activities and the shift in fecal bacterial composition were less pronounced than expected based on current literature in other species. The nutraceutical and therapeutical applications of Spirulina in companion animals are thus largely unexplored.…”
Section: Introductionmentioning
confidence: 99%